2021
DOI: 10.1038/s41467-021-26851-2
|View full text |Cite
|
Sign up to set email alerts
|

Tau activates microglia via the PQBP1-cGAS-STING pathway to promote brain inflammation

Abstract: Brain inflammation generally accompanies and accelerates neurodegeneration. Here we report a microglial mechanism in which polyglutamine binding protein 1 (PQBP1) senses extrinsic tau 3R/4R proteins by direct interaction and triggers an innate immune response by activating a cyclic GMP-AMP synthase (cGAS)-Stimulator of interferon genes (STING) pathway. Tamoxifen-inducible and microglia-specific depletion of PQBP1 in primary culture in vitro and mouse brain in vivo shows that PQBP1 is essential for sensing-tau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 90 publications
3
79
0
Order By: Relevance
“…Longitudinal PET studies have discovered a strong relationship between Aβ and tau amyloid deposition and neuroinflammation [59]. Very recent studies have shown that tau protein (the other key player in the progression of AD) interacts with the intracellular polyglutamine binding protein 1 (PQBP1), and thereby, it activates pro-inflammatory genes that induce inflammation [60]. In a mouse model of AD, the R47H-TREM2 mutation induced NDD by robustly increasing pro-inflammatory cytokines via hyperactivation of AKT signalization [61].…”
Section: Extracellular Molecular Regulators In Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal PET studies have discovered a strong relationship between Aβ and tau amyloid deposition and neuroinflammation [59]. Very recent studies have shown that tau protein (the other key player in the progression of AD) interacts with the intracellular polyglutamine binding protein 1 (PQBP1), and thereby, it activates pro-inflammatory genes that induce inflammation [60]. In a mouse model of AD, the R47H-TREM2 mutation induced NDD by robustly increasing pro-inflammatory cytokines via hyperactivation of AKT signalization [61].…”
Section: Extracellular Molecular Regulators In Neuroinflammationmentioning
confidence: 99%
“…The IL-17 cytokine family contains several Longitudinal PET studies have discovered a strong relationship between Aβ and tau amyloid deposition and neuroinflammation [59]. Very recent studies have shown that tau protein (the other key player in the progression of AD) interacts with the intracellular polyglutamine binding protein 1 (PQBP1), and thereby, it activates pro-inflammatory genes that induce inflammation [60].…”
Section: Extracellular Molecular Regulators In Neuroinflammationmentioning
confidence: 99%
“…Polyglutamine binding protein 1 (PQBP1) triggers an innate immune response by activating the cGAS-STING pathway and is needed for sensing-tau to induce nuclear translocation of nuclear factor κB (NF-κB). In addition, PQBP1 shows an intracellular receptor in the cGAS-STING pathway for cDNA of human immunodeficiency virus (HIV) and the transmissible neurodegenerative disease protein tau ( Jin et al., 2021 ). Dapsone (4,4′-diaminodiphenyl sulfone, DDS) has been linked to an impact on the regulation of NLRP3, which activates mild cognitive impairment (MCI), AD, and SARS-CoV-2-associated acute respiratory distress syndrome (ARDS) ( Namba et al., 1992 ; McGeer et al., 1992 , 1994 ; Lee et al., 2020b , 2021 ; Kanwar et al., 2021 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyglutamine binding protein 1 (PQBP1) triggers an innate immune response by activating the cGAS-STING pathway and is needed for sensing-tau to induce nuclear translocation of nuclear factor κB (NFκB). In addition, PQBP1 shows an intracellular receptor in the cGAS-STING pathway for cDNA of human immunode ciency virus (HIV) and the transmissible neurodegenerative disease protein tau 9 . Dapsone (4,4'-diaminodiphenyl sulfone, DDS) has been linked to an impact on the regulation of NLRP3, which activates mild cognitive impairment (MCI), AD, and SARS-CoV-2-associated acute respiratory distress syndrome (ARDS) [10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…The 3022 VRD participants who received the dapsone intervention (M = 201, SD = 34) compared to the 3961 VRD participants in the control group (M = 264, SD= 84) demonstrated signi cantly better peak ow scores, t(28) = -2.7, p = .0135 . Dapsone acts like PQBP1 in the cGAS-STING pathway for cDNA of HIV and the transmissible neurodegenerative disease protein tau9 .…”
mentioning
confidence: 99%